2021
DOI: 10.3390/jcm10081577
|View full text |Cite
|
Sign up to set email alerts
|

Public Concerns during the COVID-19 Lockdown: A Multicultural Cross-Sectional Study among Internet Survey Respondents in Three Countries

Abstract: (1) Background: this study aimed to evaluate the worries, anxiety, and depression in the public during the initial coronavirus disease 2019 (COVID-19) pandemic lockdown in three culturally different groups of internet survey respondents: Middle Eastern (Israel), European (Poland), and North American (Canada). (2) Methods: a cross-sectional online survey was conducted in the mentioned countries during the lockdown periods. The survey included a demographic questionnaire, a questionnaire on personal concerns, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Although the pandemic affects everyone, the intensity and severity of the response may vary depending on the latitude. Such comparisons between three different countries were presented by Emodi-Perlman et al 61. They found that Polish participants showed the second largest concern for mental health and relationships with relatives and friends.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the pandemic affects everyone, the intensity and severity of the response may vary depending on the latitude. Such comparisons between three different countries were presented by Emodi-Perlman et al 61. They found that Polish participants showed the second largest concern for mental health and relationships with relatives and friends.…”
Section: Discussionmentioning
confidence: 79%
“…Such comparisons between three different countries were presented by Emodi-Perlman et al . 61 They found that Polish participants showed the second largest concern for mental health and relationships with relatives and friends.…”
Section: Discussionmentioning
confidence: 99%
“…However, the economic and social costs of these strategies are substantial, as unemployment has surged in many countries, economic and trade activities have been severely affected, and social risks and vulnerabilities have emerged [ 5 , 6 ]. Moreover, social isolation brings on or exacerbates mental health problems [ 7 , 8 , 9 ]. Individuals feel fear, sadness, anxiety, and face worry and isolation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, parent ratings of home-quarantine impact in Israel may differ from those of other populations. Indeed, studies comparing the Israeli general population with populations in the US, Poland, and Canada have reported that Israeli participants reported less anxiety and depression following the Covid-19 outbreak 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%